ВЗАИМОДЕЙСТВИЯ СЕМЬИ И ШКОЛЫ, НАПРАВЛЕННОЕ НА САМОРЕАЛИЗАЦИЮ УЧАЩЕГОСЯ - Оразбаева, Г.Ж. (SCIENCE and SOCIETY, 2020)
The article discusses questions about the school and the family, which is designed to ensure the unity of teachers and parents, they are obliged to help the family of each student in the formation of an independent personality being, able to think extraordinarity, act, actively make decisions and bear responsibility for them, analyze and predict situations, etc. a. personality capable of being realized in modern sociocultural conditions.
Keywords: school; family; teacher; parents; education; self-realization